EFL Student Writers‘ Engagement Strategies in Technology-Mediated Communication - Dian Inayati (PAROLE: Journal of Linguistics and Education, 2021)
The pivotal role of readers/audience in helping shape students’ writing has led to attempts to engage them in their composition. This reader awareness is further enhanced with the integration of Web 2.0 technology, say blogs, into writing pedagogy. This study aims to investigate the engagement strategies EFL writers employ in their blogs, and the readers’ responses toward the strategies. In this content analysis study, twenty-seven learning English blog entries retrieved from three student bloggers were analyzed using Hyland’s (2005) and Myers’ (2010) engagement strategies. The findings reveal the student bloggers’ use of almost all the eleven engagement strategies proposed in the model albeit the extent of which varied depending on the type of the blog post, their personal background, and writing purposes. The use of such strategies as “Pronoun” and “Image” drew numerous comments from readers on the blogs, implying a strong sense of readership. It is thus recommended for EFL writing teachers to introduce varieties of engagement strategies within digitally-mediated writing environments to their students to enhance reader/writer interactions.